High-fluidity magnetic composite material and preparation method thereof

By using high spherical metal soft magnetic powder and specific ratio epoxy resin, combined with organic acid passivation treatment, the problem of insufficient flowability and magnetic properties of existing magnetic composite materials is solved, and a magnetic composite material with high flowability and good magnetic properties is achieved.

CN119752099AActive Publication Date: 2025-04-04DAYOU SCIENTFIC & TECHNICAL CO LTD

Patent Information

Application Number
CN202411731698.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing magnetic composite materials have shortcomings in terms of fluidity and magnetic properties, and it is difficult to meet the needs of different applications.

Method used

High spherical metal soft magnetic powder is used, and the flowability and magnetic properties of the composite material are improved through organic acid passivation and the use of epoxy resin.

Benefits of technology

It achieves high flowability and good magnetic properties of magnetic composite materials, meets different application needs, and ensures the uniformity and consistency of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752099A_ABST
    Figure CN119752099A_ABST
Patent Text Reader

Abstract

The invention discloses a high-fluidity magnetic composite material and a preparation method thereof.The preparation method comprises the steps that metal soft magnetic powder with the high sphericity degree is provided, and the metal soft magnetic powder has the first particle size, the second particle size and the third particle size; grading the metal soft magnetic powder corresponding to the first particle size, the second particle size and the third particle size according to a preset mixing ratio, weighing a preset weight, and mixing to obtain a first mixture; respectively weighing an organic acid accounting for a first weight ratio of the first mixture and a diluent accounting for a second weight ratio of the first mixture, and adding the diluted organic acid into the first mixture to obtain a second mixture; weighing epoxy resin accounting for a third weight ratio of the first mixture, adding the epoxy resin into the second mixture, and mixing; after the epoxy resin and the second mixture are mixed for a preset time, the high-fluidity magnetic composite material is obtained. The invention aims to meet the requirements of the existing market on different specific magnetic composite materials by manufacturing the high-fluidity magnetic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a high-fluidity magnetic composite material and a preparation method thereof. Background Art

[0002] Magnetic composite materials, as a new type of functional material combining magnetic particles and basic materials (such as polymers, metals, etc.), have shown broad application prospects in many fields such as electronics, medicine, aerospace, and automobiles. These materials have excellent performance in electronic performance, magnetic properties, and structural characteristics, providing important support for technological innovation and development in various industries.

[0003] As a new type of functional material, magnetic composite materials have shown broad application prospects and huge market potential in many fields. With the continuous advancement of technology and the continuous expansion of application fields, magnetic composite materials will play an important role in more fields and promote the innovation and development of various industries. Under such application prospects, the present invention proposes a method for preparing a high-fluidity magnetic composite material to meet the existing market demand for magnetic composite materials with different characteristics. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-fluidity magnetic composite material and a preparation method thereof, aiming to meet the existing market demand for different specific magnetic composite materials by preparing high-fluidity magnetic composite materials.

[0005] The first aspect of the present invention is to provide a method for preparing a high-fluidity magnetic composite material, the preparation method comprising:

[0006] Provide a metal soft magnetic powder with high sphericity, wherein the metal soft magnetic powder has a first particle size, a second particle size and a third particle size respectively; the first particle size is 85 μm-90 μm, the second particle size is 30 μm-35 μm, and the third particle size is 8 μm-12 μm;

[0007] The metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size are graded according to a preset mixing ratio, and a preset weight of the metal soft magnetic powder is weighed and added to a mixing device for mixing to obtain a first mixture; the mixing ratio of the metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size is 1:3:9;

[0008] Weighing an organic acid accounting for a first weight ratio of the first mixture and a diluent accounting for a second weight ratio of the first mixture respectively, mixing the organic acid and the diluent to obtain a diluted organic acid, adding the diluted organic acid to the first mixture and adding the diluted organic acid to a mixing device for mixing to obtain a second mixture;

[0009] Weighing an epoxy resin accounting for a third weight ratio of the first mixture, adding the epoxy resin to the second mixture and adding the epoxy resin to a mixing device for mixing; the molecular weight of the epoxy resin is 20000 g / mol-80000 g / mol;

[0010] After the epoxy resin and the second mixed material are mixed for a preset time, a high-fluidity magnetic composite material is obtained.

[0011] According to one aspect of the above technical solution, a preset weight of metal soft magnetic powder is weighed and added into a mixing device for mixing to obtain a first mixture, and the mixing speed is 50 r / min and the mixing time is 10 min.

[0012] According to one aspect of the above technical solution, the weight of the metal soft magnetic powder to be mixed is 10 kg;

[0013] The first weight ratio of the organic acid to the first mixture is 1%, and the second weight ratio of the diluent to the first mixture is 3%.

[0014] According to one aspect of the above technical solution, the organic acid is acetic acid and the diluent is ethanol.

[0015] According to one aspect of the above technical solution, in the step of adding the diluted organic acid to the first mixture and adding the mixture to a mixing device for mixing to obtain the second mixture, the mixing conditions include:

[0016] Maintain a non-vacuum sealed environment, an ambient temperature of 40°C and a mixing speed of 50 r / min.

[0017] According to one aspect of the above technical solution, after adding the diluted organic acid to the first mixed material and adding it to a mixing device for mixing, the preparation method further comprises:

[0018] The organic acid is mixed with the first mixed material and then passed through a 60-mesh sieve to obtain a passivated second mixed material.

[0019] According to one aspect of the above technical solution, the third weight ratio of the epoxy resin to the first mixture is 6%;

[0020] Wherein, in the step of adding the epoxy resin to the second mixture and adding the mixture into a mixing device for mixing, the mixing conditions include:

[0021] A non-vacuum sealed environment, an ambient temperature of 70°C and a mixing speed of 40 r / min were maintained.

[0022] According to one aspect of the above technical solution, the mixing time of the epoxy resin and the second mixture is 15 minutes.

[0023] The second aspect of the present invention is to provide a high-fluidity magnetic composite material, which is prepared by the preparation method described in the above technical solution.

[0024] Compared with the prior art, the high-fluidity magnetic composite material of the present invention has the following beneficial effects:

[0025] 1. Use high sphericity powder for mixing. Spherical particles can roll and slide better with each other during the mixing process, so that the mixed magnetic composite material has good uniformity and consistency, reducing the friction between particles and thus improving fluidity.

[0026] 2. The powder surface is treated by organic acid passivation to form a surface layer with organic functional groups on its surface, which has better compatibility with the resin matrix, thereby improving fluidity.

[0027] 3. Adopt the golden ratio grading ratio (large, medium and small according to the golden ratio of 1:3:9) to create good magnetic properties.

[0028] 4. The use of special medium molecular weight (20000-80000g / mol) epoxy resin ensures high fluidity and appropriate curing time of the composite material, preventing the curing time window from being too short, resulting in premature curing and loss of fluidity, while also giving the cured material a certain strength and toughness.

[0029] 5. Use a diluent to dilute the resin, reduce the viscosity of the base resin, improve its mixing effect, make the material disperse more evenly, and prevent the performance of the composite material from being affected by uneven dispersion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0031] Figure 1 The figure is a schematic diagram of a process for preparing a high-fluidity magnetic composite material in one embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. Several embodiments of the present invention are shown in the accompanying drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0034] The first aspect of the present invention is to provide a method for preparing a high-fluidity magnetic composite material, the preparation method comprising:

[0035] Provide a metal soft magnetic powder with high sphericity, wherein the metal soft magnetic powder has a first particle size, a second particle size and a third particle size respectively; the first particle size is 85 μm-90 μm, the second particle size is 30 μm-35 μm, and the third particle size is 8 μm-12 μm;

[0036] The metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size are graded according to a preset mixing ratio, and a preset weight of the metal soft magnetic powder is weighed and added to a mixing device for mixing to obtain a first mixture; the mixing ratio of the metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size is 1:3:9;

[0037] Weighing an organic acid accounting for a first weight ratio of the first mixture and a diluent accounting for a second weight ratio of the first mixture respectively, mixing the organic acid and the diluent to obtain a diluted organic acid, adding the diluted organic acid to the first mixture and adding the diluted organic acid to a mixing device for mixing to obtain a second mixture;

[0038] Weighing an epoxy resin accounting for a third weight ratio of the first mixture, adding the epoxy resin to the second mixture and adding the epoxy resin to a mixing device for mixing; the molecular weight of the epoxy resin is 20000 g / mol-80000 g / mol;

[0039] After the epoxy resin and the second mixed material are mixed for a preset time, a high-fluidity magnetic composite material is obtained.

[0040] Furthermore, a preset weight of metal soft magnetic powder is weighed and added into a mixing device for mixing to obtain a first mixed material. The mixing speed is 50 r / min and the mixing time is 10 min.

[0041] Further, the weight of the metal soft magnetic powder for mixing is 10 kg;

[0042] The first weight ratio of the organic acid to the first mixture is 1%, and the second weight ratio of the diluent to the first mixture is 3%.

[0043] Furthermore, the organic acid is acetic acid, and the diluent is ethanol.

[0044] Furthermore, in the step of adding the diluted organic acid to the first mixture and adding the mixture to a mixing device for mixing to obtain the second mixture, the mixing conditions include:

[0045] Maintain a non-vacuum sealed environment, an ambient temperature of 40°C and a mixing speed of 50 r / min.

[0046] Furthermore, after adding the diluted organic acid to the first mixed material and adding it to a mixing device for mixing, the preparation method further comprises:

[0047] The organic acid is mixed with the first mixed material and then passed through a 60-mesh sieve to obtain a passivated second mixed material.

[0048] Further, the epoxy resin accounts for 6% of the first mixture by weight;

[0049] Wherein, in the step of adding the epoxy resin to the second mixture and adding the mixture into a mixing device for mixing, the mixing conditions include:

[0050] A non-vacuum sealed environment, an ambient temperature of 70°C and a mixing speed of 40 r / min were maintained.

[0051] Furthermore, the mixing time of the epoxy resin and the second mixture is 15 minutes.

[0052] The second aspect of the present invention is to provide a high-fluidity magnetic composite material, which is prepared by the preparation method described in the above technical solution.

[0053] Compared with the prior art, the high-flow magnetic composite material and the preparation method thereof shown in the present invention have the following beneficial effects:

[0054] 1. Use high sphericity powder for mixing. Spherical particles can roll and slide better with each other during the mixing process, so that the mixed magnetic composite material has good uniformity and consistency, reducing the friction between particles and thus improving fluidity.

[0055] 2. The powder surface is treated by organic acid passivation to form a surface layer with organic functional groups on its surface, which has better compatibility with the resin matrix, thereby improving fluidity.

[0056] 3. Adopt the golden ratio grading ratio (large, medium and small according to the golden ratio of 1:3:9) to create good magnetic properties.

[0057] 4. The use of special medium molecular weight (20000-80000g / mol) epoxy resin ensures high fluidity and appropriate curing time of the composite material, preventing the curing time window from being too short, resulting in premature curing and loss of fluidity, while also giving the cured material a certain strength and toughness.

[0058] 5. Use a diluent to dilute the resin, reduce the viscosity of the base resin, improve its mixing effect, make the material disperse more evenly, and prevent the performance of the composite material from being affected by uneven dispersion.

[0059] Embodiment 1

[0060] See also Figure 1 The first embodiment of the present invention provides a method for preparing a high-fluidity magnetic composite material, comprising steps S10 to S50:

[0061] Step S10, providing a metallic soft magnetic powder with high sphericity, wherein the metallic soft magnetic powder has a first particle size, a second particle size and a third particle size respectively.

[0062] Among them, the metal soft magnetic powder can be made of soft magnetic materials allowed in the art, including but not limited to carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder. At least one of the powders, and the soft magnetic metal powder must be a powder with high sphericity.

[0063] By way of example and not limitation, in this embodiment, the metal soft magnetic powder is Fe-Si alloy soft magnetic powder, but is not limited to this material, and other metal soft magnetic powders not listed are also applicable.

[0064] Specifically, the first particle size of the metal soft magnetic powder is a large particle size powder, and its D50 (i.e., the medium particle size or median particle size) is 85μm-90μm, the second particle size of the metal soft magnetic powder is a medium particle size powder, and its D50 is 30μm-35μm, and the third particle size of the metal soft magnetic powder is a small particle size powder, and its D50 is 8μm-12μm.

[0065] Step S20, grading the metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size according to a preset mixing ratio, and weighing a preset weight of the metal soft magnetic powder and adding it into a mixing device for mixing to obtain a first mixture.

[0066] In this embodiment, the metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size are graded according to a mixing ratio of 1:3:9, and then 10 kg of the metal soft magnetic powder with high sphericity after grading is weighed and poured into a mixing equipment with a rotation speed of 50 r / min and a mixing time of 10 min.

[0067] Step S30, respectively weighing an organic acid accounting for a first weight ratio of the first mixture and a diluent accounting for a second weight ratio of the first mixture, mixing the organic acid and the diluent to obtain a diluted organic acid, adding the diluted organic acid to the first mixture and adding it to a mixing device for mixing to obtain a second mixture.

[0068] In this embodiment, the organic acid is acetic acid, and the first weight ratio of acetic acid to the first mixture is 1%. The diluent is ethanol, and the second weight ratio of ethanol to the first mixture is 3%.

[0069] Specifically, 1% acetic acid and 3% ethanol, which account for the weight of the first mixture (i.e., the graded metal soft magnetic powder), are weighed and mixed evenly. The mixture is then poured into a mixing device and mixed thoroughly in a non-vacuum enclosed space at a temperature of 40°C and a rotation speed of 50 r / min. After the diluent is fully volatilized by the weight loss method, the mixture is sieved through a 60-mesh sieve to obtain the passivated second mixture, i.e., the metal soft magnetic powder passivated by an organic acid.

[0070] Step S40, weighing an epoxy resin accounting for a third weight ratio of the first mixture, adding the epoxy resin to the second mixture and adding the epoxy resin to a mixing device for mixing.

[0071] In this embodiment, the epoxy resin is an epoxy resin with a medium molecular weight (20000 g / mol-80000 g / mol).

[0072] Specifically, weigh 6% of the weight of the first mixture (i.e., the graded metal soft magnetic powder) with a medium molecular weight epoxy resin, add the epoxy resin to a mixing device and mix it with the second mixture, and mix them in a non-vacuum closed space at a temperature of 70°C and a rotation speed of 40r / min.

[0073] In addition, ethanol accounting for 6% of the weight of the first mixture (i.e. the graded metal soft magnetic powder) is added to the mixing device at the same time as the epoxy resin to be mixed with the second mixture. Specifically, the epoxy resin and the ethanol are pre-mixed uniformly, and then added to the mixing device to be mixed with the second mixture.

[0074] Step S50, after the epoxy resin and the second mixture are mixed for a preset time, a high-fluidity magnetic composite material is obtained.

[0075] Among them, epoxy resin and ethanol are added to the second mixture for 15 minutes. After the mixing is completed, the mixture is taken out to obtain a high-fluidity magnetic composite material, which is used to make magnetic powder type and the like.

[0076] The fluidity test was conducted on the magnetic composite material prepared by the preparation method shown in this embodiment. The results are shown in Table 1.

[0077] The magnetic composite material prepared by the preparation method shown in this embodiment was tested for inductance, magnetic permeability and loss performance under different frequencies and magnetic field strengths. The results are shown in Table 2

[0078] The fluidity test was conducted on the magnetic composite material prepared by the preparation method shown in this embodiment. The results are shown in Table 3.

[0079] The fluidity test was conducted on the magnetic composite material prepared by the preparation method shown in this embodiment. The results are shown in Table 4.

[0080] Embodiment 2

[0081] The second embodiment of the present invention, also known as comparative example 1, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment. The difference lies in the change in the sphericity of the metal soft magnetic powder, namely the Fe-Si alloy soft magnetic powder. In this embodiment, Fe-Si alloy soft magnetic powder with low sphericity is used, and the remaining steps, parameters, and the amount of auxiliary materials added are the same as those in the first embodiment.

[0082] The fluidity test of the magnetic composite material prepared by the preparation method shown in this embodiment was carried out, and the results are shown in Table 1.

[0083] Embodiment 3

[0084] The third embodiment of the present invention, namely comparative example 2, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment. The difference lies in the change in the sphericity of the metal soft magnetic powder, namely the Fe-Si alloy soft magnetic powder. Crushed Fe-Si alloy soft magnetic powder is used in this embodiment, and the remaining steps, parameters, and the amount of auxiliary materials added are the same as those in the first embodiment.

[0085] The fluidity test was conducted on the magnetic composite materials prepared by the methods shown in the first to third embodiments. The results are shown in Table 1.

[0086] Table 1

[0087] sample weight pressure temperature Holding time Flow length Implementation Case 1 80g 15Mpa 175℃ 35s 170mm Implementation Case 2 80g 15Mpa 175℃ 35s 80mm Implementation Case 3 80g 15Mpa 175℃ 35s 40mm

[0088] It can be seen from the results in Table 1 above that under the same pressure, temperature, holding time and weight, the magnetic composite material prepared by the same preparation method using a metal soft magnetic powder with higher sphericity has better fluidity. For example, the flow length of the magnetic composite material prepared by the preparation method shown in the first embodiment reaches 170 mm, and the fluidity is better than that of the second embodiment and the third embodiment.

[0089] Embodiment 4

[0090] The fourth embodiment of the present invention, namely comparative example three, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment. The difference lies in the change in the particle size distribution of the metal soft magnetic powder, namely the Fe-Si alloy soft magnetic powder. In this embodiment, the metal soft magnetic powder is all Fe-Si alloy powder with a first particle size (i.e., large particle size), and its D50 is 85μm-90μm. The remaining steps, parameters, and the amount of auxiliary materials added are the same as those in the first embodiment.

[0091] The magnetic composite material prepared by the method of this embodiment was tested for inductance, magnetic permeability, and loss performance at different frequencies and magnetic field intensities. The results are shown in Table 2.

[0092] Embodiment 5

[0093] The fourth embodiment of the present invention, also known as comparative example 4, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, the difference lies in the change in the particle size distribution of the metal soft magnetic powder, i.e., the Fe-Si alloy soft magnetic powder. In this embodiment, the metal soft magnetic powder is all Fe-Si alloy powder with a third particle size (i.e., small particle size), and its D50 is 8μm-12μm. The remaining steps, parameters, and the amount of auxiliary materials added are the same as those in the first embodiment.

[0094] The magnetic composite material prepared by the method of this embodiment was tested for inductance, magnetic permeability, and loss performance at different frequencies and magnetic field intensities. The results are shown in Table 2.

[0095] Embodiment 6

[0096] The sixth embodiment of the present invention, namely comparative example five, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, the difference lies in the change in the particle size distribution of the metal soft magnetic powder, namely the Fe-Si alloy soft magnetic powder. In this embodiment, the metal soft magnetic powder adopts a Fe-Si alloy powder with a first particle size: third particle size of 1:2, and its D50 is 8μm-12μm. The remaining steps, parameters, and the amount of auxiliary materials added are the same as those in the first embodiment.

[0097] The magnetic composite materials prepared by the preparation methods shown in the fourth to sixth embodiments were tested for inductance, magnetic permeability, and loss performance at different frequencies and magnetic field intensities. The results are shown in Table 2.

[0098] Table 2

[0099]

[0100] It can be concluded from Table 2 that the size of the powder particle size directly affects the magnetic properties of the composite material. The fourth embodiment uses large-particle powders. Through testing, it is found that the magnetic composite material made of large-particle powders has high magnetic permeability, but the loss is also very high. The fifth embodiment uses small-particle powders. Through testing, it is found that the loss of the magnetic composite material made of small-particle powders is very low, but the magnetic permeability is not high. The sixth embodiment uses conventional particle sizes for grading. Through testing, it is found that the composite material made of powders after large and small particle size grading has relatively high magnetic permeability and low loss.

[0101] Combining Table 1 and Table 2, the first embodiment uses the golden ratio of 1:3:9 proposed in the present invention to grade the metal soft magnetic powder. The test results show that the golden ratio grading ratio proposed in the first embodiment of the present invention has higher magnetic permeability and lower loss than the conventional grading ratio.

[0102] Embodiment 7

[0103] The seventh embodiment of the present invention, also known as comparative example six, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment. The difference lies in the type of passivator in step S30. This embodiment uses inorganic acid (phosphoric acid), and the remaining steps, parameters, and the amount of auxiliary materials added are the same as those in Example 1.

[0104] The fluidity test was conducted on the magnetic composite materials prepared by the preparation methods shown in the first embodiment and the seventh embodiment. The results are shown in Table 3.

[0105] Table 3

[0106] sample weight pressure temperature Holding time Flow length Implementation Case 1 80g 15Mpa 175℃ 35s 170mm Implementation Case 7 80g 15Mpa 175℃ 35s 105m

[0107] From the data results in Table 3, it can be concluded that under the same pressure, temperature, holding time and weight, the magnetic composite material produced by passivating the surface of the metal soft magnetic powder with an organic acid has better fluidity than that produced by passivating the surface of the metal soft magnetic powder with an inorganic acid.

[0108] Embodiment 8

[0109] The eighth embodiment of the present invention, also known as comparative example seven, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, the difference being the molecular weight of the epoxy resin in step S40. This embodiment uses a small molecular weight epoxy resin with a molecular weight of less than 20,000 g / mol, and the remaining steps, parameters, and the amount of auxiliary materials added are the same as those in Example 1.

[0110] The fluidity test was conducted on the magnetic composite material prepared by the preparation method shown in this embodiment. The results are shown in Table 4.

[0111] Embodiment 9

[0112] The ninth embodiment of the present invention, namely, embodiment eight, also provides a method for preparing a high-fluidity magnetic composite material. The preparation method shown in this embodiment is basically the same as the preparation method shown in the first embodiment, the difference lies in the molecular weight of the epoxy resin in step S40. This embodiment uses a small molecular weight epoxy resin with a molecular weight of more than 80,000 g / mol, and the remaining steps, parameters, and the amount of auxiliary materials added are the same as those in embodiment one.

[0113] The fluidity test of the magnetic composite material prepared by the preparation method shown in this embodiment is carried out, and the results are shown in Table 4:

[0114] Table 4

[0115] sample weight pressure temperature Holding time Flow length Curing time Implementation Case 1 80g 15Mpa 175℃ 35s 170mm 1min20s Implementation Case 8 80g 15Mpa 175℃ 35s 200mm 20s Implementation Case 9 80g 15Mpa 175℃ 35s 60mm 4min

[0116] From the data results in Table 4, it can be concluded that under the same pressure, temperature, holding time and weight, the use of low molecular weight epoxy resin can make the composite material have super high fluidity, but at the same time the curing time of the composite material will be very fast, which may cause the composite material to cure prematurely and lose fluidity; while the use of high molecular weight epoxy resin will make the composite material have very poor fluidity and a long curing time.

[0117] Therefore, the use of the special medium molecular weight epoxy resin proposed in the first embodiment of the present invention not only ensures the high fluidity of the magnetic composite material, but also ensures an appropriate curing time, which can prevent the magnetic composite material from prematurely curing due to too fast a curing time and thus losing fluidity, and also enables the magnetic composite material to have a certain strength and toughness after curing.

[0118] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0119] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high-fluidity magnetic composite material, characterized in that: The preparation method comprises: Provide a metal soft magnetic powder with high sphericity, wherein the metal soft magnetic powder has a first particle size, a second particle size and a third particle size respectively; the first particle size is 85 μm-90 μm, the second particle size is 30 μm-35 μm, and the third particle size is 8 μm-12 μm; The metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size are graded according to a preset mixing ratio, and a preset weight of the metal soft magnetic powder is weighed and added to a mixing device for mixing to obtain a first mixture; the mixing ratio of the metal soft magnetic powders corresponding to the first particle size, the second particle size and the third particle size is 1:3:9; Weighing an organic acid accounting for a first weight ratio of the first mixture and a diluent accounting for a second weight ratio of the first mixture respectively, mixing the organic acid and the diluent to obtain a diluted organic acid, adding the diluted organic acid to the first mixture and adding the diluted organic acid to a mixing device for mixing to obtain a second mixture; Weighing an epoxy resin accounting for a third weight ratio of the first mixture, adding the epoxy resin to the second mixture and adding the epoxy resin to a mixing device for mixing; the molecular weight of the epoxy resin is 20000 g / mol-80000 g / mol; After the epoxy resin and the second mixed material are mixed for a preset time, a high-fluidity magnetic composite material is obtained.

2. The method for preparing a high-fluidity magnetic composite material according to claim 1, characterized in that: In the step of weighing a preset weight of metal soft magnetic powder and adding it into a mixing device for mixing to obtain a first mixed material, the mixing speed is 50 r / min and the mixing time is 10 min.

3. The method for preparing a high-fluidity magnetic composite material according to claim 1, characterized in that: The weight of the metal soft magnetic powder to be mixed is 10 kg; The first weight ratio of the organic acid to the first mixture is 1%, and the second weight ratio of the diluent to the first mixture is 3%.

4. The method for preparing a high-fluidity magnetic composite material according to claim 3, characterized in that: The organic acid is acetic acid, and the diluent is ethanol.

5. The method for preparing a high-fluidity magnetic composite material according to claim 1, characterized in that: In the step of adding the diluted organic acid to the first mixed material and adding the mixed material to a mixing device for mixing to obtain a second mixed material, the mixing conditions include: Maintain a non-vacuum sealed environment, an ambient temperature of 40°C and a mixing speed of 50 r / min.

6. The method for preparing a high-fluidity magnetic composite material according to claim 5, characterized in that: After adding the diluted organic acid to the first mixed material and adding the mixed material to a mixing device for mixing, the preparation method further comprises: The organic acid is mixed with the first mixed material and then passed through a 60-mesh sieve to obtain a passivated second mixed material.

7. The method for preparing a high-fluidity magnetic composite material according to claim 1, characterized in that: The epoxy resin accounts for 6% of the first mixture by weight; Wherein, in the step of adding the epoxy resin to the second mixture and adding the mixture into a mixing device for mixing, the mixing conditions include: A non-vacuum sealed environment, an ambient temperature of 70°C and a mixing speed of 40 r / min were maintained.

8. The method for preparing a high-fluidity magnetic composite material according to claim 7, characterized in that: The mixing time of the epoxy resin and the second mixture is 15 minutes.

9. A high-fluidity magnetic composite material, characterized in that: The high-fluidity magnetic composite material is prepared by the preparation method according to any one of claims 1-8.

Citation Information

Patent Citations

  • High-filling-rate metal soft magnetic powder material and preparation method thereof

    CN110176337A

  • Preparation method of high-frequency wide-temperature low-coercivity iron-based soft magnetic composite material

    CN116598085A

  • Soft magnetic composite material for fluid filling process

    US20220359109A1

  • Magnetic powder for manufacturing magnet, and magnet and magnetic element

    WO2022241736A1

Cited By

  • High-stability integrated low-voltage molded inductor and preparation method thereof

    CN121260655A

  • Composite magnetic material, preparation method thereof and magnetic device

    CN121528672A